2020
DOI: 10.1111/psyp.13559
|View full text |Cite
|
Sign up to set email alerts
|

Better cognitive efficiency is associated with increased experimental anxiety

Abstract: There is increased interest in the development of cognitive training targeting working memory (WM) to alleviate anxiety symptoms, but the effectiveness of such an approach is unclear. Improved understanding of the effect of cognitive training on anxiety may facilitate the development of more effective cognitive training treatment for anxiety disorders. This study uses an experimental approach to examine the interplay of WM and anxiety following WM training. Previous studies show that increased demand on WM red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It has been shown that a threat of shock can modulate working memory performance in an N-back task 37 . The implementation of a distractor task after the encoding trials successfully blocked the rehearsal (silent repeating or elaboration) of information, as suggested by the absence of a recency effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a threat of shock can modulate working memory performance in an N-back task 37 . The implementation of a distractor task after the encoding trials successfully blocked the rehearsal (silent repeating or elaboration) of information, as suggested by the absence of a recency effect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies in normative samples that we are aware of only report the mean trait anxiety scores of their participants without performing any correlations between trait anxiety and physiological measures (e.g. 9,64,[71][72][73] , with the exception of 42 ). Future experiments should therefore further examine the interactions between (shock-and scream-induced) state anxiety and temperamental trait anxiety disposition.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up work employing a within-subjects manipulation of threat conditions (acute and sustained, along with no-threat) would be particularly informative with respect to directly comparing the effects of different threat types on cognitive performance and their relationship to individual difference factors. Such work could help to interface findings from the current work with an emerging literature regarding the effects of predictable and unpredictable threat on cognitive performance (Balderston et al, 2020; Grillon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%